Retinol Promotes In Vitro Growth of Proximal Colon Organoids through a Retinoic Acid-Independent Mechanism. - Taichi Matsumoto (PLoS ONE, 2016)
Retinol (ROL), the alcohol form of vitamin A, is known to control cell fate decision of various types of stem cells in the form of its active metabolite, retinoic acid (RA). However, little is known about whether ROL has regulatory effects on colonic stem cells. We examined in this study the effect of ROL on the growth of murine normal colonic cells cultured as organoids. As genes involved in RA synthesis from ROL were differentially expressed along the length of the colon, we tested the effect of ROL on proximal and distal colon organoids separately. We found that organoid forming efficiency and the expression level of Lgr5, a marker gene for colonic stem cells were significantly enhanced by ROL in the proximal colon organoids, but not in the distal ones. Interestingly, neither retinaldehyde (RAL), an intermediate product of the ROL-RA pathway, nor RA exhibited growth promoting effects on the proximal colon organoids, suggesting that ROL-dependent growth enhancement in organoids involves an RA-independent mechanism. This was confirmed by the observation that an inhibitor for RA-mediated gene transcription did not abrogate the effect of ROL on organoids. This novel role of ROL in stem cell maintenance in the proximal colon provides insights into the mechanism of region-specific regulation for colonic stem cell maintenance.